Globalization of the financial sector of the Republic of Kazakhstan - Kazbekov Bibolatova, B. A. K. D. (Journal of Economic Research & Business Administration, 2016)
This article discusses the current state of the transformation of the international financial system in global awareness-financial complex, characterized by fierce competition. Analyzed globalization creates a single world financial market, whose influence on the development of national economies is comparable to the impact of other countries. Themselves as global capital markets are regulated primarily at the national level that poses a threat to system financial crisis that will affect all countries. This article focuses on the globalized financial market. One of the most important trends of the modern world economy has been the rapid economic growth in developing countries. Special attention in this work paid to the main tendencies of development of Bank sector of the Republic of Kazakhstan for the period till 2020 and its relationship with globalization. Identified positive and negative aspects of world globalization process.